White adipose tissue development in zebrafish is regulated by both developmental time and fish size - Imrie, Dru; Sadler, Kirsten C. (Developmental dynamics, 2010)
Adipocytes are heterogeneous. Whether their differences are attributed to anatomical location or to different developmental origins is unknown. We investigated whether development of different white adipose tissue (WAT) depots in zebrafish occurs simultaneously or whether adipogenesis is influenced by the metabolic demands of growing fish. Like mammals, zebrafish adipocyte morphology is distinctive and adipocytes express cell‐specific markers. All adults contain WAT in pancreatic, subcutaneous, visceral, esophageal, mandibular, cranial, and tail‐fin depots. Unlike most zebrafish organs that form during embryogenesis, WAT was not found in embryos or young larvae. Instead, WAT was first identified in the pancreas on 12 days postfertilization (dpf), and then in visceral, subcutaneous, and cranial stores in older fish. All 30 dpf fish exceeding 10.6 mm standard length contained the adult repertoire of WAT depots. Pancreatic, esophageal, and subcutaneous WAT appearance correlated with size, not age, as found for other features appearing during postembryonic zebrafish development. Developmental Dynamics 239:3013–3023, 2010. © 2010 Wiley‐Liss, Inc.